Hubungan Efikasi Diri Remaja dengan Pengetahuan, Sikap dan Praktik Pencegahan Infeksi COVID-19: Indonesia - Lestari, Puspita Hanggit; Juliani, Enni; Rosliany, Nia (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2022)
Covid-19 has spread all over the world. All ages are at risk for COVID-19 infection, including adolescents who are at risk of contracting COVID-19 because of their high activity and tend to gather in groups. The impact of COVID-19 on adolescents can affect physical and mental health. This study was to obtain an overview of adolescent self-efficacy related to the prevention of COVID-19 infection and the knowledge, attitudes and COVID-19 prevention practices in adolescents. The study used a cross sectional method involving 389 adolescents with purposive sampling and snow ball sampling techniques. The results showed that the adolescent self-efficacy variable was 59.1% in the high category, adolescent knowledge was 66.8% in the low category, the attitude of preventing COVID-19 was found to be 55% in the low category, and the practice of preventing COVID-19 was 49.6% in the low category. The results of the analysis of the relationship between self-efficacy and COVID-19 prevention practices obtained a significant relationship between self-efficacy and COVID-19 prevention practices (p value = 0.012) and OR value = 1.679. Adolescents who have high self-efficacy have good COVID-19 prevention practices. The findings can be used to develop health promotions that aim to increase the prevention of COVID-19 in the youth aggregate.